2016
DOI: 10.1111/jsr.12483
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual differences in the dynamics of the homeostatic process are trait‐like and distinct for sleep versus wakefulness

Abstract: The sleep homeostatic Process S reflects the build-up of sleep pressure during waking and its dissipation during sleep. Process S is modelled as a saturating exponential function during waking and a decreasing exponential function during sleep. Slow wave activity is a physiological marker for non-rapid eye movement (non-REM) sleep intensity and serves as an index of Process S. There is considerable interindividual variability in the sleep homeostatic responses to sleep and sleep deprivation. The aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…The underlying mechanisms of these stable inter-individual differences are still unclear, and may involve genetic factors (De Gennaro et al, 2008;Landolt, 2011) or differences in structural anatomy (Buchmann et al, 2011). This is further expanded upon by findings showing that the dynamics of the homoeostatic process itself are trait-like (Rusterholz, Durr, & Achermann, 2010;Rusterholz, Tarokh, Van Dongen, & Achermann, 2017). How these features relate to trait-like characteristics observed with IQ, vulnerability to sleep loss or progression of disease remain to be elucidated.…”
Section: Intra-class Correlation Coefficient Metricsmentioning
confidence: 99%
“…The underlying mechanisms of these stable inter-individual differences are still unclear, and may involve genetic factors (De Gennaro et al, 2008;Landolt, 2011) or differences in structural anatomy (Buchmann et al, 2011). This is further expanded upon by findings showing that the dynamics of the homoeostatic process itself are trait-like (Rusterholz, Durr, & Achermann, 2010;Rusterholz, Tarokh, Van Dongen, & Achermann, 2017). How these features relate to trait-like characteristics observed with IQ, vulnerability to sleep loss or progression of disease remain to be elucidated.…”
Section: Intra-class Correlation Coefficient Metricsmentioning
confidence: 99%
“…The MEQ is the oldest, most cited, and one of the most predominantly used measures in chronobiology and sleep research despite its self-reported and thus subjective nature (see Adan et al 2012 for a comprehensive review). This is possibly so because scores in the MEQ have been shown to be valid by predicting objective and subjective measures, such as intrinsic circadian period (Duffy et al 2001), alternations in temperature (Bailey and Heitkemper 2001) and cognition throughout the day (Yoon et al 1998), circadian secretion of melatonin (Kantermann et al 2015) and cortisol (Bailey and Heitkemper 2001), patterns of reported sleep and wake times , and capacity to adapt to night shifts and presence of sleep disorders (Sack et al 2007). This questionnaire enquires about preferred rather than actual timings, and scores vary between individuals due to sociocultural factors (Biswas et al 2014;Natale et al 2009), age (Adan and Almirall 1990;Duffy et al 2001), sex (Adan and Natale 2002), heritability (Hida et al 2014;von Schantz et al 2015), and geographical characteristics, such as latitude (e.g., Miguel et al 2017) and longitude (e.g., Shawa and Roden 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Assuming the unidimensionality of the MEQ would mean that M-E is guided by a single process. However, to understand individual differences in this respect, it must be considered that these cycles reflect the interplay between Process C, which depends on time of day (circadian time), and Process S, determined by the duration of wakefulness (Borbély 1982;Dijk and Lockley 2002) and efficiency in dissipating this need during sleep (Rusterholz et al 2016), as explained above. Additionally, some individuals display what has been termed a bimodal response, characterized as simultaneously signs of extreme morning and evening types (Martynhak et al 2010;Tempaku et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Stable and trait-like interindividual differences are observed in physiological responses to TSD, particularly in polysomnographic sleep and slow-wave energy responses to sleep loss across 2–3 days 12 14 , as well as in heart rate, heart rate variability, percentage of eyelid closure (PERCLOS), blink rate, and EEG alpha power across 2.5–15 months 15 . Furthermore, energy balance responses to sleep loss are phenotypic and stable across long time intervals of up to 2,132 days 16 and across different types of sleep loss with 4 days between exposures 17 (i.e., acute TSD and chronic SR).…”
Section: Introductionmentioning
confidence: 99%